Integrating crops and livestock for improved food security and livelihoods in rural Zimbabwe - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
The overall goal of the project is to identify, test and prove ways to increase agricultural production, improve household food security, and alleviate poverty, thereby reducing food-aid dependency in rural Zimbabwe through better-integrated crop and livestock production and market participation. The project’s research will also test ways to improve linkages amongst market chain actors that allow smallholder enterprises to actually exploit these.